A Glance Upon Material for the Spine, by Steve Paxton - Marengo, Mayana; Muniz (Universidade do Estado de Santa Catarina – UDESC, Florianópolis/SC, Brazil), Zilá (Revista Brasileira de Estudos da Presença, 2022)
The present research highlights some key points from Material for the Spine, by Steve Paxton, to establish links between Paxton’s work and positions on phenomena of sensation and perception in the context of contemporary performance. It also analyzes the relationship between internal body sensation and the design of the moving body, which Paxton defines as form. From these concepts, the present paper discusses the artistic power of this approach, based on a scenic practice which aim is to create dance.